A comparative pan-genomic analysis of 53 C. pseudotuberculosis strains based on functional domains - Bernardes, Juliana S.; Eberle, Raphael J. [UNESP]; Vieira, Fabio R. J.; Coronado, Mônika A. [UNESP] (Taylor & Francis, 2020)
Corynebacterium pseudotuberculosis is a pathogenic bacterium with great veterinary and economic importance. It is classified into two biovars: ovis, nitrate-negative, that causes lymphadenitis in small ruminants and equi, nitrate-positive, causing ulcerative lymphangitis in equines. With the explosive growth of available genomes of several strains, pan-genome analysis has opened new opportunities for understanding the dynamics and evolution of C. pseudotuberculosis. However, few pan-genomic studies have compared biovars equi and ovis. Such studies have considered a reduced number of strains and compared entire genomes. Here we conducted an original pan-genome analysis based on protein sequences and their functional domains. We considered 53 C. pseudotuberculosis strains from both biovars isolated from different hosts and countries. We have analysed conserved domains, common domains more frequently found in each biovar and biovar-specific (unique) domains. Our results demonstrated that biovar equi is more variable; there is a significant difference in the number of proteins per strains, probably indicating the occurrence of more gene loss/gain events. Moreover, strains of biovar equi presented a higher number of biovar-specific domains, 77 against only eight in biovar ovis, most of them are associated with virulence mechanisms. With this domain analysis, we have identified functional differences among strains of biovars ovis and equi that could be related to niche-adaptation and probably help to better understanding mechanisms of virulence and pathogenesis. The distribution patterns of functional domains identified in this work might have impacts on bacterial physiology and lifestyle, encouraging the development of new diagnoses, vaccines, and treatments for C. pseudotuberculosis diseases. Communicated by Ramaswamy H. Sarma.
Keywords: biovar equi; biovar ovis; C. pseudotuberculosis; functional domains and pan-genomic analyses